Produktivitas Kerja Karyawan ditinjau dari Tingkat Pendidikan dan Motivasi Kerja Pada Perusahaan Rina Jaya Tahun 2014 - Yunus, Taufiq, Drs. Djoko Suwandi., SE, M.Pd (2015)
The purpose of this study were: 1) To know the effect level education on the level of employee productivity Rina Jaya Manang 2014.2) To know the effect of motivation on the level of labor productivity Rina Jaya employees Manang 2014. 3) To know the effect level education and motivation of the employee productivity levels Rina Jaya Manang, 2014. This associative quantitative research took place in the company Rina Jaya Manang 2014. Take a sample of 48 employees of the population of 57 employees, data collection techniques using the questionnaire technique. Analysis techniques the data used to test the hypothesis is linear regression analysis double, t test and F addition is done in the calculation of the coefficients determination, the relative contribution and donations effectively. The conclusion of this study were: 1) There is a positive effect of educational level on employee productivity at the company Rina Jaya Manang. 2) There is a positive influence on work motivation on employee productivity the company Rina Jaya Manang. 3) There is a positive effect of educational level and motivation to work productivity of employees at the company Rina Jaya Manang. From the analysis of data obtained by the coefficient of determination R2 0,445 which showed that the combination of variables level education and motivation by 44.5%, while the remaining 55.5% influenced by other variables not examined. Kata Kunci: Produktivitas Kerja, Tingkat Pendidikan dan Motivasi Kerja